Coping Strategies of Early Childhood in Terms of Sex Perspective in PGRI 44 Rogojembangan Kindergarten Tembalang, Semarang - Wulandari, Catur; Hartati, Sri Eni (Indonesian Journal of Early Childhood Education Studies, 2014)
Child interactions encountered some problems frequently. The ability to deal with problems is one of the capability that should be owned by children. Coping strategies will be useful for the child to deal with various situations both external and internal problems. Subjects in this study consisted of one teacher, two parents, and two students. Data collection techniques were using of interview, observation and documentation. This study used a method of qualitative research. This research method was used because of the researchers want to reveal the differences of coping strategies used by both children, boy, and girl when faced with the problems of social and emotional. The data analysis in this study was using data analysis interactive of Miles and Huberman model. It involves several processes including data collection, data reduction, data presentation, conclusion, and verification. The results showed that children have been able to report various forms of coping strategies. The coping strategies include seeking support (ask for help), problem-solving (solving problems), distraction (distracting), and escape (away / escape). The girl reported more dominant in seeking support strategies than a boy. Coping response with aggressive and destructive behavior more often indicated by boy than a girl.How to citeWulandari, C., & Hartati, S. (2014). Coping Strategies of Early Childhood in Terms of Sex Perspective in PGRI 44 Rogojembangan Kindergarten Tembalang, Semarang. Indonesian Journal Of Early Childhood Education Studies, 3(1), 37-41. doi:10.15294/ijeces.v3i1.9474